Rice Protein Matrix Enhances Circulating Levels of Xanthohumol Following Acute Oral Intake of Spent Hops in Humans - O'Connor, Annalouise; Konda, Veera; Reed, Ralph L.; Christensen, J. Mark; Stevens, Jan F.; Contractor, Nikhat (Molecular nutrition & food research, 2018)
Scope Xanthohumol (XN), a prenylated flavonoid found in hops, exhibits anti‐inflammatory and antioxidant properties. However, poor bioavailability may limit therapeutic applications. As food components are known to modulate polyphenol absorption, the objective is to determine whether a protein matrix could enhance the bioavailability of XN post oral consumption in humans. Methods and results This is a randomized, double‐blind, crossover study in healthy participants (n = 6) evaluating XN and its major metabolites (isoxanthohumol [IX], 6‐ and 8‐prenylnaringenin [6‐PN, 8‐PN]) for 6 h following consumption of 12.4 mg of XN delivered via a spent hops‐rice protein matrix preparation or a control spent hops preparation. Plasma XN and metabolites are measured by LC–MS/MS. Cmax, Tmax, and area‐under‐the‐curve (AUC) values were determined. Circulating XN and metabolite response to each treatment was not bioequivalent. Plasma concentrations of XN and XN + metabolites (AUC) are greater with consumption of the spent hops‐rice protein matrix preparation. Conclusion Compared to a standard spent hops powder, a protein‐rich spent hops matrix demonstrates enhanced plasma levels of XN and metabolites following acute oral intake. The limited bioavailability of the phytochemical xanthohumol is inhibiting its therapeutic applications. It is investigated whether a special preparation could enhance its bioavailability in humans after an acute intake. By comparing the plasma levels of xanthohumol (and metabolites) up to 6 h after participants ingested xanthohumol via a spent hops‐rice protein matrix preparation or a control spent hops preparation, it is found that the protein matrix enhances the bioavailability of xanthohumol.